Determination of Antibacterial Evaluation, Phytochemical Screening and Ascorbic Acid Assay of Turmeric (Curcuma longa) - Oghenejobo, Michael; Opajobi, O. A.; Bethel, U. S. Oghenejobo; Uzuegbu, U. E. (Challenges and Advances in Pharmaceutical Research Vol. 1, 2022)
Using the agar well diffusion method, the microbial susceptibility of an ethanolic extract of Turmeric (Curcuma longa) was tested. The extract was found to be active against the bacteria used as it inhibited all the organisms with the highest inhibition zone of 13.7mm recorded against Shigella flexnerri and the least inhibition of 2.3mm recorded against Staphylococcus epidermis. Minimum Inhibitory Concentration (MIC) values range from 6.25mg/ml to 200mg/ml. Shigella flexnerri gave MIC of 6.25mg/ml, S. aureus and K. Pneumonia, 25mg/ml, E. coli, 50mg/ml, S. epidermis, Lactobacillus and P. aeruginosa, 100mg/ml and V. cholera and S. typhi 200mg/ml respectively. Secondary metabolites were also screened using phytochemistry. Fourteen (14) secondary metabolites were screened from the ethanolic extract. The presence of these phytochemicals like tannins, alkaloids, phenols, steroids, flavonoids, phlobatannin, cardiac glycosides, terpenoids, triterpenes, saponin, etc; is indicative of the antimicrobial activity of Turmeric. The extract was found to contain 66.749mg/100ml ascorbic acid which is relatively comparable to many fruits recommended by dieticians. The value of curcumin present (Rf value 0.436) is also relatively close to that of pure curcumin. The results so far obtained are indicative of the good medicinal value of Turmeric in both pharmaceutical and pharmacological formulations. It is recommended therefore that further research should be done on it for its use as a plant medicinal especially in this period that herbal drugs are becoming significant as antimicrobials.